Development And Evaluation Of Resilience Training Module: Its Effect On Resilience Among Caregivers - Wah, Tze Huey (2018)
Caregiving can be overwhelming if the role has demanded more than it is expected. As resilience has a positive relationship with surviving life crises, enhancing resilience will provide them with skills to cope and decrease depression. Caregivers can learn resilience skills to take proactive steps to prevent crisis or to reduce risk factors. The objectives of this study are to develop module to enhance resilient skill and evaluate the effectiveness of the module in enhancing resilience of caregivers. Structural Equation Modeling has supported the conceptual framework of this study, where the construct resilience has five subconstructs (problem solving, spirituality, leadership, self-efficacy and networking). Resilience scale RS-14 (questionnaire with Likert Scale) and reflective journaling have been used to collect data to address the effectiveness of the training module. This is a quasi experiment, applying mixed method design with both quantitative and qualitative data analysis. A purposive sampling of one hundred caregivers have participated in this resilience training. A paired sample t test of resilience score for pre and post resilience training is significantly different with p < .05. The post training score is significantly higher than the pre training score which is supported by testimonials of participants. The participants have improved their level of resilience after the training with no lag behind in anyone particular subconstructs. Although a one-way between-groups analysis of variance has shown a significance difference in gained score of subconstructs, the post-hoc comparison using the Tukey HSD test has indicated that the differences of gained scores among the five subconstructs were quite small and not significance.